2013
DOI: 10.1136/bmjqs-2013-002039
|View full text |Cite
|
Sign up to set email alerts
|

Assessing adverse events among home care clients in three Canadian provinces using chart review

Abstract: ObjectivesThe objectives of this study were to document the incidence rate and types of adverse events (AEs) among home care (HC) clients in Canada; identify factors contributing to these AEs; and determine to what extent evidence of completion of incident reports were documented in charts where AEs were found.MethodsThis was a retrospective cohort study based on expert chart review of a random sample of 1200 charts of clients discharged in fiscal year 2009–2010 from publicly funded HC programmes in Manitoba, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 20 publications
4
77
0
3
Order By: Relevance
“…Two recent studies, one conducted in the USA (Madigan 2007 ) and the other in Canada , found that 13 % of home care patients experienced an adverse event. Larger estimates based on expert chart review of 1200 patients discharged in [2009][2010] in Canada showed a rate of 4.4 % adverse events (Blais et al 2013 ). The most frequent were injuries from falls, wound infections, behavioural or mental health problems and adverse outcomes from medication errors.…”
Section: Adverse Events In Home Carementioning
confidence: 99%
“…Two recent studies, one conducted in the USA (Madigan 2007 ) and the other in Canada , found that 13 % of home care patients experienced an adverse event. Larger estimates based on expert chart review of 1200 patients discharged in [2009][2010] in Canada showed a rate of 4.4 % adverse events (Blais et al 2013 ). The most frequent were injuries from falls, wound infections, behavioural or mental health problems and adverse outcomes from medication errors.…”
Section: Adverse Events In Home Carementioning
confidence: 99%
“…[1][2][3][4][5][6][7] As defined by the Canadian Patient Safety Institute (CPSI), patient safety is "the pursuit of the reduction and mitigation of unsafe acts within the healthcare system, as well as the use of best practices shown to lead to optimal patient outcomes". [6] In recognition of high error rates the Institute of Medicine (IOM) mandated that there be improvements to health education programs by increasing the amount of content related to safety.…”
Section: Introductionmentioning
confidence: 99%
“…It might be an event or occurrence which becomes apparent during the delivery of care services and which has a negative or potentially negative impact on patient care [3]. The same characteristic can be found in the definition proposed by The Institute of Medicine (IOM) in the USA, which indicates that an AE results in unintended harm to the patient by an act of commission or omission, rather than by the underlying disease or condition of the patient [4]. The Joint Commission [5], an independent, non-profit organization, which accredits and certifies more than 20,000 health care organizations and programs in the United States defines AE as an untoward, undesirable, and usually unanticipated event, such as the death of a patient.…”
Section: Introductionmentioning
confidence: 82%